Flora w mikrotoponimii powiatu sokólskiego - Filinowicz, Alina (Acta Polono-Ruthenica, 2018)
In the article the author described microtoponymy of the sokólski district containing in their formative root vegetative terms being used by the locals. She also directed attention to a typically border-character of the analysed region. Sokólski district is located in the central part of Podlasie voivodeship next to the Belorussian border. Since time immemorial, it has been a place of connection for Baltic and Slavonic people with Eastern and Western Slavs. Ethnically and linguistically diversified settlement processes of the analysed region were reflected in the place names. There are not only Polish place names, but also the East Slavic, Baltic as well as hybrid Polish-Belorussian and Slavonic-Baltic forms.